Hepatoprotective effects of Huangqi decoction (Astragali Radix and Glycyrrhizae Radix et Rhizoma) on cholestatic liver injury in mice: Involvement of alleviating intestinal microbiota dysbiosis. (1st March 2021) - Zou, Juan; Li, Wenkai; Wang, Guofeng; Fang, Su; Cai, Jingyi; Wang, Tianming; Zhang, Hua; Liu, Ping; Wu, Jiasheng; Ma, Yueming
Abstract: Ethnopharmacological relevance: Gut microbiome dysbiosis is closely associated with cholestatic liver disease. Huangqi decoction (HQD), a traditional herbal formula, has protection against cholestatic liver injury. However, the effect of HQD on gut microbiome remains unknown. Aim of the study: To investigate the effect of HQD on 3, 5-diethoxycarbonyl-1, 4-dihydrocollidine (DDC) induced cholestatic liver injury and its effect on the gut microbiome profiles. Materials and methods: Mice with DDC-induced cholestatic liver injury were treated with low and high doses of HQD for 8 weeks. Fecal samples were analyzed by 16 S ribosomal DNA sequencing. Barrier function as well as intestinal and hepatic inflammation was analyzed by real-time PCR and western blotting. Results: HQD treatment ameliorated the DDC-induced liver injury and collagen deposition around hepatic bile ducts. Moreover, decreased diversity, reduced richness, and abnormal composition of intestinal microbiota of cholestatic mice were remarkably attenuated by HQD supplementation. Differences in bacterial abundance, including levels of Prevotellaceae_NK3B31_group, Alistipes, and Gordonibacter, were increased in DDC-induced mice, as compared with control mice, and were decreased after HQD treatment. Moreover, intestinal dysbiosis promoted disruption of the intestinal barrier in cholestatic mice. However, HQD treatment alleviated intestinal barrier dysfunction. Importantly, increased hepatic expression of pro-inflammatory factors and the NLRP3 inflammasome, which have a positive correlation with differential bacteria, were characteristics found in DDC-induced cholestatic mice that were alleviated upon treatment with HQD. Conclusion: HQD treatment alleviated gut microbiota dysbiosis, ameliorated the intestinal barrier dysfunction, inhibited liver inflammation, and protected against DDC-induced cholestatic liver injury. Graphical abstract: Image 1